Cytochrome P450 2U1 Is a Novel Independent Prognostic Biomarker in Breast Cancer Patients - Luo, Bin; Chen, Chuang; Wu, Xiaoyan; Yan, Dandan; Chen, Fangfang; Yu, Xinxin; Yuan, Jingping (Frontiers in Oncology, 2020)
Background: The susceptibility of breast cancer is largely affected by the metabolic capacity of breast tissue. This ability depends in part on the expression profile of cytochrome P450 (CYPs). CYPs are a superfamily of enzymes with related catalytic properties to exogenous and endogenous compounds, including xenobiotic metabolism, drugs, and some endogenous substances metabolism which activate cells and stimulate cell signaling pathways, such as arachidonic acid metabolism, steroid metabolism, fatty acid metabolism. Interestingly, CYP was electively expressed in different tumors, and mediated the metabolic activation of multiple carcinogens and participated in the inactivation and activation of anticancer drugs. However, the role of cytochrome P450 2U1 (CYP2U1) in breast cancer is still poorly understood. Methods: To explore the biological value of CYP2U1 in breast cancer, we performed immunohistochemical(IHC) analysis and survival analysis based on clinico- pathological data of breast cancer. Results: IHC analysis showed that the abundance of CYP2U1 protein was inversely proportional to the state of estrogen receptor(ER) (P<0.05), and the lower the degree of tumor differentiation, the higher the protein abundance(P<0.001). Additionally, compared with luminal tumors, the CYP2U1 protein content was more abundant in triple negative breast cancer (P<0.05). Importantly, survival analysis showed that higher CYP2U1 protein levels predicted poor 5-year overall survival rate (P<0.01), 5-year disease-free survival rate (P<0.05), and 5-year metastatic-free survival rate(P<0.01) for the entire enrolled breast cancer patients. Conclusions: CYP2U1 is generally closely related to the clinicopathological characteristics and is also an adverse prognostic factor for breast carcinoma patients, indicating that CYP2U1 is involved in the progression of breast cancer.